Data-driven elections: implications and challenges for democratic societies - Colin J. Bennett; David Lyon (Internet Policy Review, 2019)
There is a pervasive assumption that elections can be won and lost on the basis of which candidate or party has the better data on the preferences and behaviour of the electorate. But there are myths and realities about data-driven elections. It is time to assess the actual implications of data-driven elections in the light of the Facebook/Cambridge Analytica scandal, and to reconsider the broader terms of the international debate. Political micro-targeting, and the voter analytics upon which it is based, are essentially forms of surveillance. We know a lot about how surveillance harms democratic values. We know a lot less, however, about how surveillance spreads as a result of democratic practices – by the agents and organisations that encourage us to vote (or not vote). The articles in this collection, developed out of a workshop hosted by the Office of the Information and Privacy Commissioner for British Columbia in April 2019, address the most central issues about data-driven elections, and particularly the impact of US social media platforms on local political institutions and cultures. The balance between rights to privacy, and the rights of political actors to communicate with the electorate, is struck in different ways in different jurisdictions depending on a complex interplay of various legal, political, and cultural factors. Collectively, the articles in this collection signal the necessary questions for academics and regulators in the years ahead.
Keywords: 300; Micro-targeting; Political behavourial targeting; Political micro-targeting; Surveillance; Big data; Social media platforms